The Intellectual Contribution of Fahrur Razi Abdillah to Qira’at Literacy: A Study of the Book Al-Muyassar fī al-Qira’at al-Sab’ - Ali Abdur Rohman; Mazroatul Ainia; Rohmah Sari Dewi (ZAD Al-Mufassirin, 2026)
This study aims to answer the research questions regarding the distinctive characteristics, systematic writing methodology of the book Al-Muyassar fī al-Qira’at al-Sab’ by KH. Fahrur Razi Abdillah, and its specific contributions to contemporary qira'at science. Employing a qualitative research design with a content analysis approach, this library research examines the primary text in depth. The findings indicate that the hallmark of Al-Muyassar lies in its highly structured organization, meticulously detailed presentation of jam'u al-qira’at, and communicative linguistic style. Its writing system systematically begins with the complete presentation of Qur'anic verses, followed by the use of a specific color-coding mechanism to isolate words containing recitation variants, a guide for the jam' sequence, and comprehensive explanations paired with textual evidence ('adillah) from Matan al-Shatibiyyah. Amidst the lineage of celebrated qira'at texts in Indonesia, such as Faidhul Barakat and Mamba'ul Barakat, the theoretical contribution of this book lies in expanding the treasury of qira'at scholarship by introducing a more refined dimension to the jam' methodology through a clear, intuitive, and highly accessible content organization for readers, without reducing the validity of traditional, sanad-based qira'at knowledge.